الذاكرة الدلالية لدى التلاميذ ذوي عسر القراءة - سعد العايب, جهيدة; شنة, محمد رضا (جامعة الوادي - University of Eloued, 2022)
ملخص : تهدف الدراسة إلى التعرف على مستوى الذاكرة الدلالية لدى التلاميذ ذوي عسر القراءة وذلك بالإعتماد على منهج دراسة الحالة عن طريق أدوات المقابلة وتطبيق الإختبارات على العينة المختارة بأسلوب غير عشوائي وبطريقة قصدية وتتكون من تلميذ وتلميذة يتمدرسون بالصف الرابع ابتدائي. وبعد إجراء الدراسة تم التوصل إلى أنه: لا يوجد لدى تلميذ السنة الرابعة ابتدائي ذو عسر القراءة ضعف أدائي في أبعاد تسمية الصور، التعرف على أطراف الجسم، الفهم بالربط الوظيفي للجمل، الحكم على الأشياء بالربط الدلالي، السيولة اللفظية والتقطيع الدلالي، التعرف على أصوات المحيط، الرسم الدلالي الموجه. في حين أنه يوجد لدى تلميذ السنة الرابعة ابتدائي ذو عسر القراءة ضعف أدائي في بعدي التصنيف والترتيب الدلالي، والمعجم الدلالي المصور. Abstract : The study aims to identify the level of semantic memory among students who have difficult to read (pupils with dyslexia) by using the case study method interview tools, and applying tests on the selected sample in a non-random and intentional with tow pupils (male and female) student who are studying in the fourth primary school year .After the study, it was found that: The fourth year of primary school pupil with dyslexia has no performance weakness in dimensions naming images, recognizing the body's limbs, understanding of the functional linkage of sentences, judging things by semantic connection, verbal fluidity and semantic cut, recognition of environment sounds. Whereas the fourth year of primary school pupil with dyslexia has a poor weakness performance in the dimensions of classification and semantic ranking, and the semantic correct of images
مقال
Keywords: ذاكرة دلالية ذاكرة المعاني عسر القراءة; Semantic memory ; meaning memory ; dyslexia